Comparison between nonlocal effects and coupled channels in a simple nuclear fusion model - Galetti, D. [UNESP]; Cândido Ribeiro, M. A. [UNESP] (American Physical Society (APS), 1995)
It is discussed how the introduction of a nonlocal potential in the relative coordinate of a nuclear collision described by a simple model Hamiltonian can also account for an enhancement in the nuclear fusion cross section. The interplay between this effect and the channel coupling interaction is studied in this simple model and their different contributions to the fusion cross sections are analyzed. © 1995 The American Physical Society.